Analisis Minat Penggunaan Aplikasi PLN Mobile Pada Generasi Milenial: Studi Kasus Mahasiswa Fakultas Syariah dan Dakwah IAIN Sorong - Efa Rubawati Syaifuddin; Muhammad Husen; Rahmawati Sukma Lestari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
PT PLN (Persero) has developed and adopted a digital application platform which aims to make things easier for the public through the synergy of PLN services to customers through digital-based applications. This research aims to find out how much influence or positive impact is provided by BUMN through the PLN mobile application to the community, especially the millennial generation. This research explains the usability level of the PLN mobile application through a quantitative approach using descriptive analysis. Obtained data Using systematic random sampling data collection techniques from 100 respondents and 60% of respondents who knew the PLN Mobile application, the results showed that KPI and Economics study program students were the ones who knew the most about the PLN Mobile application and 40 people (40%) answered " don't know about the PLN mobile application.